Hubungan Efektifitas Supervisi Kepala Sekolah Dengan Kinerja Guru Dalam Pembelajaran Di SD Inpres 10/73 Bulu-Bulu - Bahar, Haryani; Wahira, Wahira; Pada, Amir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study is an ex post-facto research that aims to find out whether there is  a relationship between the effectiveness of principal supervision and teacher performance in learning at SD Inpres 10/73 bulu. The independent variable in this study is the effectiveness of the head of the school, while the bound variable is the performance of the teacher. The population in this study is all school teachers in SD Inpres 10/73 Bulu-Bulu, while the sample of teachers at SD Inpres 10/73 Bulu-Bulu is 12 teachers. The data of the research results was obtained by distributing written questionnaires in the form of questionnaires. Data analysis techniques in quantitative research use statistics, namely descriptive statistics and inferential statistics. The results of the study show that the supervision of the principal shows very effective results and the performance of teachers in learning shows very effective results. There is a positive and significant relationship between the supervision of the principal and the performance of teachers at SD Inpres 10/73 Bulu-Bulu, Tonra District, Bone Regency.